2018
DOI: 10.1016/j.diii.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting inferior vena cava (IVC) filter retrievability using positional parameters: A comparative study of various filter types

Abstract: Shorter dwell time, lower mean tilt, caudal migration and less caval wall penetration are positive predictors of successful IVC filter retrieval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Other studies have also documented a propensity for ALN filters to tilt. A study by Gotra et al found that ALN filters have the highest mean absolute value of tilt at 5.6 degrees when compared to other retrievable filters [19]. In another retrospective, multicenter study, 37 out of 123 patients had moderate tilting of the ALN filter and 6 patients had severe tilting of more than 15-degree deviation from the IVC axis [20].…”
Section: Alnmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have also documented a propensity for ALN filters to tilt. A study by Gotra et al found that ALN filters have the highest mean absolute value of tilt at 5.6 degrees when compared to other retrievable filters [19]. In another retrospective, multicenter study, 37 out of 123 patients had moderate tilting of the ALN filter and 6 patients had severe tilting of more than 15-degree deviation from the IVC axis [20].…”
Section: Alnmentioning
confidence: 95%
“…The ALN (ALN Implants)filter is a stainless-steel retrievable filter cleared by FDA in 2008 (Figure 7) [1,11]. The 6 shorter struts are used to adhere the filter to the walls of the vena cava while the 3 longer struts are designed to position the filter centrally along the vena cava [19]. Of note, no 2 legs of the ALN are of the same length, an intended feature designed to prevent filter tilt.…”
Section: Preserve Trial Ivc Filtersmentioning
confidence: 99%
“…Common reasons for routine retrieval failure with the subsequent need for advanced retrieval techniques include severe tilt, migration, penetration into the caval wall, caval occlusion (Fig. 4), and hook embedment into the IVC wall [3,32,34,36,37,[40][41][42]. Longer filter dwell time has been associated with the need for advanced techniques for retrieval [35,41].…”
Section: Technical Aspects Of Retrievalmentioning
confidence: 99%
“…4), and hook embedment into the IVC wall [3,32,34,36,37,[40][41][42]. Longer filter dwell time has been associated with the need for advanced techniques for retrieval [35,41]. Advanced techniques have reported success rates of 62.9-100% and lead to higher IVCF retrieval rates, up to 98.2% [27•, 36, 37, 40, 43•].…”
Section: Technical Aspects Of Retrievalmentioning
confidence: 99%
“…The 2010 FDA safety communication raised clinician awareness that retrievable IVC filters can in fact be challenging to remove. Significant filter tilt, an embedded filter, a caval strut perforation, a filter fracture, or the presence of thrombus within the filter — in addition to ordinary tissue ingrowth and strut epithelialization — can make retrieval problematic [50, 51]. Dinglassan et al [52] examined preretrieval filter characteristics noted by CT that were associated with complicated retrieval procedures, comparing 48 patients with complicated retrievals versus 48 control patients with uncomplicated retrievals.…”
Section: Clinical Rationale For the Sentry Bioconvertible Ivc Filtermentioning
confidence: 99%